Tren Insidensi Influenza A di Asia Tenggara dalam 10 Tahun Terakhir (2015–2025): Scoping Review - Sulhiani Anggraini; Nila Febriana Iswara; Muthia Cenderadewi (Malahayati Nursing Journal, 2026)
ABSTRACT Influenza A is an emerging and re-emerging infectious disease with pandemic potential, contributing significantly to global morbidity and mortality. Southeast Asia is considered a hotspot due to high population density, cross-border mobility, live poultry markets, intense human–animal interactions, and tropical–subtropical climate conditions. Despite the 2009 H1N1 pandemic demonstrating its pandemic potential, a comprehensive synthesis of Influenza A incidence in Southeast Asia over the past decade (2015–2025) remains limited. To synthesize available evidence on the incidence, circulation patterns, and epidemiological trends of Influenza A in Southeast Asia from 2015 to 2025 within the context of Global Health Security. A scoping review was conducted in 2025 following PRISMA guidelines. Literature searches were performed in PubMed, ScienceDirect, Google Scholar, DOAJ, and official WHO FluNet/GISRS databases for the period 2015–2025. Eligible sources included peer-reviewed articles and official surveillance reports in English or Indonesian focusing on Influenza A in Southeast Asia. Editorials, opinion papers, and studies conducted outside the region were excluded. Eight studies met the inclusion criteria. Influenza A circulates year-round in Southeast Asia, with seasonal peaks during high humidity and rainfall periods. Thailand experiences two annual peaks, while Laos shows a late rainy-season peak. Periodic shifts occur between A(H1N1) pdm09 and A(H3N2) due to viral evolution and population immunity. Influenza B also demonstrates alternating Victoria and Yamagata lineage patterns in several countries. Influenza activity significantly declined during 2020–2021 due to COVID-19 non-pharmaceutical interventions, followed by a rebound in 2022–2023, particularly among young children with immunity gaps. Influenza A remains a persistent and dynamic public health threat in Southeast Asia, characterized by year-round circulation and shifting subtype dominance. Strengthened surveillance systems, laboratory capacity, and regional preparedness are essential to enhance pandemic preparedness and Global Health Security. Keywords: Influenza A, Southeast Asia, Global Health Security, Surveillance, Incidence.  ABSTRAK Influenza A merupakan penyakit emerging dan re-emerging dengan potensi pandemi yang berkontribusi signifikan terhadap morbiditas dan mortalitas global. Asia Tenggara menjadi wilayah hotspot karena kepadatan penduduk tinggi, mobilitas lintas batas, pasar unggas hidup, interaksi manusia–hewan, serta iklim tropis–subtropis. Meskipun pandemi H1N1 tahun 2009 menunjukkan potensi pandemi Influenza A, belum terdapat sintesis komprehensif yang mengkaji insidensinya di Asia Tenggara selama periode 2015–2025. Menyintesis bukti ilmiah mengenai insidensi, pola sirkulasi, dan tren epidemiologi Influenza A di Asia Tenggara selama periode 2015–2025 dalam konteks ketahanan kesehatan global.Penelitian ini menggunakan desain scoping review yang dilaksanakan pada tahun 2025 dengan mengikuti pedoman PRISMA. Pencarian literatur dilakukan melalui basis data PubMed, ScienceDirect, Google Scholar, DOAJ, serta laporan resmi WHO FluNet/GISRS untuk periode 2015–2025. Kriteria inklusi meliputi artikel peer-review dan laporan surveilans resmi berbahasa Inggris atau Indonesia yang berfokus pada Influenza A di Asia Tenggara. Editorial, opini, dan studi di luar kawasan dikecualikan. Sebanyak delapan studi memenuhi kriteria inklusi. Influenza A bersirkulasi sepanjang tahun di Asia Tenggara dengan puncak musiman pada periode kelembapan dan curah hujan tinggi. Thailand mengalami dua puncak tahunan, sedangkan Laos menunjukkan puncak pada akhir musim hujan. Dominasi subtipe A(H1N1) pdm09 dan A(H3N2) bergeser secara periodik akibat evolusi virus dan imunitas populasi. Aktivitas influenza menurun signifikan pada 2020–2021 akibat intervensi non-farmasi selama pandemi COVID-19, kemudian meningkat kembali pada 2022–2023, terutama pada anak usia dini yang mengalami kesenjangan imunitas. Influenza A tetap menjadi ancaman kesehatan masyarakat yang dinamis di Asia Tenggara dengan pola sirkulasi sepanjang tahun dan pergeseran dominasi subtipe. Penguatan surveilans, kapasitas laboratorium, dan kesiapsiagaan regional sangat diperlukan untuk mendukung keamanan kesehatan global dan mitigasi potensi pandemi di masa mendatang. Kata Kunci: Influenza A, Asia Tenggara, Keamanan Kesehatan Global, Surveilans, Insidensi.